Assessment of PM2.5 sources in the Banja Luka (Bosnia and Herzegovina) suburban area using nondestructive techniques and positive matrix factorization. Issue 1 (8th December 2022) - Radenković, Mirjana B.; Topalović, Dušan B.; Radić, Ranka U.; Vukić, Ljiljana M.
Abstract: The sources of different pollutants contributing to ambient PM2.5 in the Banja Luka (Bosnia and Herzegovina) suburban area were estimated. From January 2016 to March 2017, a total of 140 daily PM2.5 filter samples were collected and analyzed by complementary nondestructive analytical techniques. Concentrations of Na, Mg, Al, Si, S, Cl, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, Br, Rb, Sr, and Pb were determined by energy dispersive X-ray fluorescence technique while black carbon concentration was estimated using multi-wavelength absorption optical measurements. Evaluation of the emission sources was performed based on the obtained PM2.5 composition data using positive matrix factorization model. The results indicate five main groups of sources contributing to the annual mean PM2.5 concentration (38.7 µg/m 3 ): secondary sulfur/coal combustion 35.4% (11.8 µg/m 3 ), biomass combustion 26.1. % (9.2 µg/m 3 ), road salts/heavy oil 21.2% (7.5 µg/m 3 ), soil dust 1.1% (0.4 µg/m 3 ) and traffic emissions less than 0.05%. Black carbon originating from diesel fuel and biomass burning was differentiated by applied optical technique and included into PMF analysis. The approach and results of the field study are unique and significant contribution to the air quality management in this area. Copyright © 2022 American Association for Aerosol Research Graphical Abstract: UF0001